The Ar-Rahnu efficiency and its determinants - Maamor, Selamah; Ismail, Abdul Ghafar (IBTRA, 2010)
Ar-Rahnu plays an important role in providing funds for micro and small enterprises.However, these enterprises could not be reached if ar-hanu is not efficient. Therefore, the aim of this paper is to measure the efficiency of ar-rahnu and identify the factors affecting the efficiency.This study uses Data Envelopment Analysis (DEA) method to estimate ar-rahnu efficiency and Tobit model to determine the efficiency of Islamic Pawnshop (ar-rahnu).We use three different types of DEA model which are technical efficiency (TE), pure technical efficiency (PTE) and scale efficiency (SE) Model.The efficiency of ar-rahnu is measured from the secondary data for 2006 across several ar-rahnu operators including Bank Rakyat, Permodalan Kelantan Berhad (PKB), Muasasah Gadaian Islam Terengganu (MGIT) and Cooperatives under Yayasan Pembangunan Ekonomi Islam Malaysia (YaPEIM).Based on the efficiency score, we find that the highest average efficiency score among categories of arahnu used is Bank Rakyat. Furthermore, most of the ar-rahnu branches operate in increasing return to scale which imply that most of them can improve their performance by increasing their inputs. While, variables that affect ar-rahnu efficiency found from this empirical study are size, financial self-sufficiency, subsidy and group of business positively affect ar-rahnu efficiency.